2011
DOI: 10.1073/pnas.1018307108
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal 3′-phosphate RNA splicing ligase characterization identifies the missing component in tRNA maturation

Abstract: Intron removal from tRNA precursors involves cleavage by a tRNA splicing endonuclease to yield tRNA 3′-halves beginning with a 5′-hydroxyl, and 5′-halves ending in a 2′,3′-cyclic phosphate. A tRNA ligase then incorporates this phosphate into the internucleotide bond that joins the two halves. Although this 3′-P RNA splicing ligase activity was detected almost three decades ago in extracts from animal and later archaeal cells, the protein responsible was not yet identified. Here we report the purification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 39 publications
(39 reference statements)
2
106
0
2
Order By: Relevance
“…RtcB proteins seem to function in most, if not all, archaea as GTP-dependent tRNA-splicing ligases and join spliced tRNA molecules halves to form mature-sized tRNAs molecules e.g., in archaeal precursor tRNA-Trp. 21 The observation that the genomes of some archaea contain 2 open reading frames, previously predicted to function as DNA ligases, led to the discovery of a putative second family of archaeal RNA ligases. 22,23 The founding member of this putative RNA ligase family is the Pyrococcus abyssi reading frame Pab1020.…”
Section: Introductionmentioning
confidence: 99%
“…RtcB proteins seem to function in most, if not all, archaea as GTP-dependent tRNA-splicing ligases and join spliced tRNA molecules halves to form mature-sized tRNAs molecules e.g., in archaeal precursor tRNA-Trp. 21 The observation that the genomes of some archaea contain 2 open reading frames, previously predicted to function as DNA ligases, led to the discovery of a putative second family of archaeal RNA ligases. 22,23 The founding member of this putative RNA ligase family is the Pyrococcus abyssi reading frame Pab1020.…”
Section: Introductionmentioning
confidence: 99%
“…(The junction phosphate in yeast tRNA splicing derives from the γ-phosphate of the NTP substrate for the 5′ kinase step.) Direct ligation languished until 2011, when three laboratories identified bacterial, archaeal, and mammalian RtcB proteins as RNA ligase enzymes capable of sealing 2′,3′ cyclic phosphate and 5′-OH ends (13)(14)(15). In support of a bona fide RNA repair function for RtcB in vivo, it was shown that E. coli RtcB is competent and sufficient for eukaryal tRNA splicing, by virtue of its ability to complement growth of yeast cells that lack the endogenous healing-and-sealing-type tRNA ligation system (16).…”
mentioning
confidence: 99%
“…T he Escherichia coli RtcB is a founding member of a recently discovered family of RNA repair/splicing enzymes that join RNA 2′,3′-cyclic-PO 4 or 3′-PO 4 ends to RNA 5′-OH ends (1)(2)(3)(4). RtcB executes a four-step pathway that requires GTP as an energy source and Mn 2+ as a cofactor (5)(6)(7).…”
mentioning
confidence: 99%